2008
DOI: 10.1002/hbm.20694
|View full text |Cite
|
Sign up to set email alerts
|

Linearity of the fMRI response in category‐selective regions of human visual cortex

Abstract: The goal of this study was to determine the linearity of the blood oxygen level-dependent (BOLD) response, as measured by functional magnetic resonance imaging (fMRI), in category-selective regions of human visual cortex. We defined regions of the temporal lobe that were selective to faces (fusiform face area, FFA) and places (parahippocampal place area, PPA). We then determined the linearity of the BOLD response in these regions to their preferred and nonpreferred stimuli. First, we tested the principle of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Second, it is reasonable to assume that any CI based upon activation in a single brain region may provide only a noisy and incomplete estimation of the overall internal template driving behavioral responses. For instance, in the case of face perception, its reliance upon an entire network of cortical regions is well‐documented [Gauthier et al, ; Haxby et al, ; Ishai et al, ; Rossion et al, ; Tsao et al, ] and consistent with the idea that these regions provide both redundant and complementary information for the purpose of face recognition [Fox et al, ; Gobbini and Haxby, ; Nestor et al, ]. Thus, the construction of hybrid CIs based from patterns of activation across multiple regions may ultimately provide a way to boost the quality of neurally‐derived CIs.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Second, it is reasonable to assume that any CI based upon activation in a single brain region may provide only a noisy and incomplete estimation of the overall internal template driving behavioral responses. For instance, in the case of face perception, its reliance upon an entire network of cortical regions is well‐documented [Gauthier et al, ; Haxby et al, ; Ishai et al, ; Rossion et al, ; Tsao et al, ] and consistent with the idea that these regions provide both redundant and complementary information for the purpose of face recognition [Fox et al, ; Gobbini and Haxby, ; Nestor et al, ]. Thus, the construction of hybrid CIs based from patterns of activation across multiple regions may ultimately provide a way to boost the quality of neurally‐derived CIs.…”
Section: Discussionmentioning
confidence: 90%
“…Second, face profile and object features encoded in the FFA are probably less diagnostic for their respective classes and, therefore, less robustly encoded—for instance, highly effective features for face detection like those shown in Figure b have difficulty in dealing with profiles. Third, the FFA does not appear to respond linearly to other categories than faces [Horner and Andrews, ] warning against the application of standard image classification to such cases. Therefore, we argue, the investigation of alternative types of stimuli in face‐selective regions is likely to be less informative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(21)). For example, Soltysik et al (23) reported that the auditory response obeys linearity for stimuli of a relatively long duration, but reveals nonlinear properties for short-duration stimuli (<10 s).…”
Section: Temporal and Spatial Characteristics Of The Hemodynamic Respmentioning
confidence: 99%
“…The failures of linearityinsuchstudies(suchasfailuresoftemporalsummation) generally don't tell us whether it is B(N ),or the neural response N , or both, that are nonlinear (Boynton & Finney, 2003, Miller, Luh, Liu, Martinez, Obata, et al, 2001Soltysik, Peck, White, Crosson, & Briggs, 2004). Generalization is problematic, because different brain regions may differ in linearity (Horner & Andrews, 2009;Soltysik et al, 2004). The authors of a study in which electrophysiological as well as fMRI measures were taken concluded that the source of nonlinearity in V1 is N ,notB(N ) (Wan,Riera,Iwata,Takahashi, Wakabahyashi, & Kawashima, 2006).…”
Section: Evidence For Linearity Of B(n ) (Proposition 1) and Nonlineamentioning
confidence: 99%